Kinetics of phagocytic activity, plaque-forming cells and specific agglutinins of turbot (Scophthalmus maximus L.) immunised with O antigen of Vibrio damsela and Pasteurella piscicida - Santarém, M. M.; Figueras Huerta, Antonio (Fish & Shellfish Immunology, 1994)
11 páginas, 1 tabla, 5 figuras The O antigens derived from Vibrio damsela and Pasteurella piscicida were evaluated to determine their ability to enhance non-specific defence mechanisms and the specific immune response in turbot. Intraperitoneal injections of 100 μg V. damsela or P. piscicida O antigen resulted in an increased phagocytic activity of splenic leucocytes 3 days after immunisation, although the level of phagocytosis of sheep red blood cells (SRBC) was always low. In both groups of immunised fish a peak in the specific plaque-forming cells (PFC) was observed 21 days post-injection. There were no differences in PFC number induced by the two bacterins in turbot. Peak antibody titres were 28 and 42 days after immunisation with O antigen from P. piscicida and V. damsela respectively. CICYT MAR91-1133-CO2-02 Peer reviewed